Asphalt Emulsions 1990
DOI: 10.1520/stp23510s
|View full text |Cite
|
Sign up to set email alerts
|

Mix Design Practices for Cold In-Place Recycled Pavements

Abstract: Since 1984, the Oregon State Highway Division has constructed 724 km (450 centerline miles) of cold in-place recycled pavements. During this period, an intensive study was undertaken by the Oregon Department of Transportation (ODOT) and Oregon State University (OSU) with the following purposes: 1. To develop an improved mix design procedure for cold in-place recycled pavements. 2. To evaluate the structural contribution of cold in-place recycled pavements. 3. To develop improved guidelines and specifications f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Results from evaluation of 52 CIR pavements indicated that 47 of the projects had good or very good performance, and only five had poor performance [28][29][30][31],…”
Section: Oregonmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from evaluation of 52 CIR pavements indicated that 47 of the projects had good or very good performance, and only five had poor performance [28][29][30][31],…”
Section: Oregonmentioning
confidence: 99%
“…These results showed that resilient modulus values in the range of 150,000 to 600,000 psi were obtained. Resilient moduli are also affected by the stiffness of RAP asphalt [29,30].…”
Section: Resilient Modulusmentioning
confidence: 99%